Disability, food insecurity by nativity, citizenship, and duration. (April 2020) - Altman, Claire E.; Heflin, Colleen M.; Patnaik, Hannah Akanksha
Abstract: Prior research examines the prevalence of either disability or food insecurity among immigrants. We examine whether the presence of a disability operates as a stronger predictor of food insecurity among prime-aged immigrants relative to the US-born. Probit models estimate the relationship of disability with food insecurity among immigrants and distinguish by duration of US residence and citizenship status using nationally representative data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2014. Descriptively, food insecurity was highest among non-citizen immigrants with longer durations of US residence, compared to non-citizen immigrants with shorter durations and naturalized immigrants. Multivariate results suggest that among Hispanics, the association between disability and food insecurity was stronger among immigrants compared to US-born adults; the disability-food insecurity association varied by an immigrant's duration of US residence and citizenship status. The results emphasize the importance of disaggregating by citizenship status and duration of US residence. Highlights: Disability and immigration status are overlapping vulnerabilities for food insecurity. Disability status exacerbates food insecurity for Hispanic immigrants. Naturalization protects immigrants from food insecurity.